Efficient gene transfer by pulse parameters for electrochemotherapy of cells in vitro and in muscle and melanoma tumors in mice - Omerzel Masa; Markelc Bostjan; Brezar Simona Kranjc; Sersa Gregor; Cemazar Maja (Radiology and Oncology, 2025)
In recent years, various gene therapy strategies have been developed for cancer treatment. One of these strategies is electroporation-based delivery of therapeutic transgenes - gene electrotransfer (GET). Electrochemotherapy and GET have been combined in several contemporary preclinical and veterinary studies. In most cases, two different pulse protocols are used, each for a specific treatment. The aim of our current study was to test whether the standard pulse protocol used in daily clinical practice for electrochemotherapy can also be used for effective GET.